The great zoo of China - Reilly, Matthew (Gallery Books, 2015)
"The all-new thriller from #1 internationally bestselling author Matthew Reilly! It is a secret the Chinese government has been keeping for forty years. They have found a species of animal no one believed even existed. It will amaze the world. Now the Chinese are ready to unveil their astonishing discovery within the greatest zoo ever constructed. A small group of VIPs and journalists has been brought to the zoo deep within China to see its fabulous creatures for the first time. Among them is Dr. Cassandra Jane "CJ" Cameron, a writer for National Geographic and an expert on reptiles. The visitors are assured by their Chinese hosts that they will be struck with wonder at these beasts, that they are perfectly safe, and that nothing can go wrong. Of course it can't... GET READY FOR ACTION ON A GIGANTIC SCALE"--